A finite temperature investigation of the Georgi-Glashow model in 3D - Biagio Lucini (Nuclear Physics B - Proceedings Supplements, 2004)
We study the SU(2) gauge theory with scalar matter in the adjoint representation in 3D at finite temperature. We find evidence for a finite temperature phase transition both in the symmetric and in the broken phase: such transitions are consistent with the universality class of Ising 2D, in agreement with recent analytical arguments.